Journeying to a Safe Space Sexual and Religious Identity Integration of Filipino LGBT-affirmative Church Members. - Evangelista, Z. M.
Identity is a complex concept. It is pluralistic and cuts across several domains. Some domain specific identities may oppose another, like in the case of sexual identity and religious identity, where successful integration is achieved for some individuals, while for others, a significant amount of conflict can occur, especially for religious sexual minorities. The present study analyzes the integration stories of members of an LGBT-affirmative church, the Metropolitan Community Church-Quezon City (MCC-QC). In two kwentuhan sessions, 12 MCCQC members shared their lived experiences of identity integration. Based on participant accounts, the process of integration began with experiences of oppression, followed by personal quests towards a deeper faith and knowledge of one?s self, and eventually culminating in a continual personalization of faith. Identity integration was facilitated by participation in a safe and supportive faith community. We found that this process is relevant especially in promoting well-being among LGBT faithful.
Keywords: Pscyhology -- Periodicals; LGBT; Identity Integration; MCC; Religion